Developing a machine learning based prognostic model and a supporting web-based application for predicting the possibility of early diabetes and diabetic kidney disease - Amin, M.M. Shahriar; Gomes, Partho Mark; Gomes, Jui Philomina; Tasneem, Faiza (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.